Relative shear stress distribution in vegetated flows : an experimental uncertainty study - Munar Marinez, William Mateo (2019)
Vegetation exerts a strong control in the morphological evolution of fluvial systems. It is therefore important to include the effects of vegetation in fluvial studies and numerical models. By assuming a momentum conservation balance, a common way to analyze the flow resistance in vegetated channels splits the total shear stress, τ, into shear stress due to vegetation (or vegetation drag), τ_v, and bed-shear stress, τ_b. However, there are no methodologies available to reduce the contribution of the bed-shear stress, when the vegetation is sparse or dense. To study the latter effect, an intense experimental investigation is carried out. The laboratory experiments are performed in a tilting flume, using rigid vegetation at three different densities and considering emergent and submerged hydraulic conditions. In all the analyzes, the experimental uncertainty was taken into account to improve the representativity of the results obtained. It was found that using the methods without uncertainties can generate errors between 0.1% and 245% and an average error of 62%, compared with the results obtained by considering the propagation of uncertainties. It was possible to develop an equation by PLS to estimate the distribution of shear forces with parameters independent of the flow and representing the characteristics of the vegetation and the channel. This model predicts enough values to represent the process with an error in the estimate of 16%. Our results of this investigation show that the bed-shear stress contribution reduces considerably in configurations where dense vegetation is present.